The Development of Teaching Materials for Chemical Bonding Course Integrated with Islamic Values: Need Analysis - Yenti, Elvi; Nazir, Nazir; Zein, Mas'ud (Journal of Natural Science and Integration, 2025)
This study aims to identify the need for the development of teaching materials for the Chemical Bonding course in the form of textbooks that integrate Islamic values. The needs analysis was conducted through an open-ended questionnaire distributed via Google Forms, which was accessible online to respondents. The subjects of this research included lecturers teaching Chemical Bonding, Basic Chemistry, and Organic Chemistry, as well as Chemistry program students who had previously studied chemical bonding concepts. A qualitative descriptive data analysis method was employed. Responses from the questionnaire were categorized and analyzed to calculate the percentage of respondents supporting the need for the development of integrated teaching materials. The results revealed unanimous agreement among lecturers (100%) on the necessity of developing chemical bonding teaching materials that incorporate Islamic values. Additionally, 95% of students expressed strong support for the development of such materials, while 5% indicated that the development of self-learning resources would also be beneficial. Based on these findings, it is evident that there is a substantial demand for a Chemical Bonding textbook integrated with Islamic values to enhance the learning experience and bridge the gap between scientific knowledge and Islamic principles.Keywords: analysis, teaching materials, chemical bonds, integration of Islamic values